The Aspiring Adept : Robert Boyle and His Alchemical Quest - Principe, Lawrence (Book collections on Project MUSE., 2000)
"The Aspiring Adept presents a provocative new view of Robert Boyle (1627-1691), one of the leading figures of the Scientific Revolution, by revealing for the first time his avid and lifelong pursuit of alchemy. Boyle has traditionally been considered, along with Newton, a founder of modern science because of his mechanical philosophy and his experimentation with the air-pump and other early scientific apparatus. However, Lawrence Principe shows that his alchemical quest - hidden first by Boyle's own codes and secrecy, and later suppressed or ignored - positions him more accurately in the intellectual and cultural crossroads of the seventeenth century."